2017
DOI: 10.15405/epsbs.2017.12.6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Literacy And Attitudes Survey (Iglas): International Population-Wide Assessment Instrument

Abstract: Genetics represents the fastest developing discipline in the history of scientific enquiry. Genetic advances have implications for individuals and society, including matters related to law, ethics, education, medicine and philosophy. As such, it will be important for all people to be able to engage with genetic research, not just at the point that it becomes personally applicable, such as in medical treatment, but also more generally across many social domains. Given the ever-increasing impact of genetics on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…The average genetic literary scores of this set of studies which use assessments adapted from the brief questionnaire range from 64.6 to 83.6% (Dar-Nimrod et al, 2019;Haga et al, 2013;Jallinoja & Aro, 1999;Molster et al, 2008;Schmidlen et al, 2016) with multiple assessment items having a correct response rate of 95% or higher (Dar-Nimrod et al, 2019;Haga et al, 2013;Schmidlen et al, 2016). Recently, the International Genetic Literacy and Attitudes Survey was developed to overcome some of the limitations of previous questionnaires including only true/false items and ceiling effects (Chapman et al, 2017). The measure includes items with high item discrimination in order to better differentiate individuals with respect to their genetic knowledge.…”
Section: Genetic Literacy In the Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The average genetic literary scores of this set of studies which use assessments adapted from the brief questionnaire range from 64.6 to 83.6% (Dar-Nimrod et al, 2019;Haga et al, 2013;Jallinoja & Aro, 1999;Molster et al, 2008;Schmidlen et al, 2016) with multiple assessment items having a correct response rate of 95% or higher (Dar-Nimrod et al, 2019;Haga et al, 2013;Schmidlen et al, 2016). Recently, the International Genetic Literacy and Attitudes Survey was developed to overcome some of the limitations of previous questionnaires including only true/false items and ceiling effects (Chapman et al, 2017). The measure includes items with high item discrimination in order to better differentiate individuals with respect to their genetic knowledge.…”
Section: Genetic Literacy In the Populationmentioning
confidence: 99%
“…and "How many copies of each gene do we have in each cell?" (Chapman et al, 2017). The study that utilized this measure found that the average genetic literacy in a large sample of individuals with secondary education was 65.5% (Chapman et al, 2019).…”
Section: Genetic Literacy In the Populationmentioning
confidence: 99%
“…The study was approved by the Goldsmiths Department of Psychology Ethics Committee, UK; and the Ethics Committee for Interdisciplinary Research of Tomsk State University, Russia. The online International Genetic Literacy and Attitudes Survey (iGLAS) was used to collect data (see [17,18]). iGLAS is a dynamic instrument, currently in its 10 th version, which consists of five parts: genetic knowledge, attitudes and opinions about genetics, demographic information, vignettes and neuromyths.…”
Section: Methodsmentioning
confidence: 99%
“…Several other researchers emphasize the importance of genetics education in nursing education (Camak, 2016;Daack-Hirsch et al, 2013;Giarelli & Reiff, 2012). In line with these studies, other researchers have also developed various genetics literacy assessment instruments, such as the genetics literacy assessment instrument for undergraduates (Bowling et al, 2008), Genetic Literacy and Attitudes Survey (Chapman, 2017), and Public Understanding and Attitudes towards Genetics and Genomics (Condit, 2010). Interestingly, in accordance with researches reviewing and raising the urgency of genetics education, these literacy instruments focus more on measuring respondents' literacy and understanding of the basic concepts of genetics, even though some of them are related to diseases and genetic testing.…”
Section: Research Rationalementioning
confidence: 95%